A novel electromagnetic bistable vibration energy harvester with an elastic boundary: Numerical and experimental study. (November 2021) - Zhang, Jingyu; Li, Xuefeng; Feng, Xingxing; Li, Renfu; Dai, Lu; Yang, Kai
Highlights: A novel bistable energy harvester with the elastic boundary (BEH_EB) is conceived. BEH_EB could enhance the inter-well responses in the low frequency band. The merit of BEH_EB's potential energy distribution is mathematically interpreted. Abstract: This paper comprehensively investigates a novel electromagnetic bistable vibration energy harvester with elastic boundary (BEH_EB). The BEH_EB consists of an inclined-spring-based bistable vibration energy harvester (BEH) and a vertically attached elastic boundary. The BEH (which does not have the elastic boundary) is employed as a comparative counterpart. Owing to the vertically attached elastic boundary of the BEH_EB, the distance between the two equilibria are wider than that of the BEH, which could enhance the inter-well response. As a result, this can significantly enhance the performance. Firstly, the governing equations of the BEH_EB are formulated, which are experimentally validated. Moreover, the experimental comparison between the BEH_EB and BEH is presented to verify the benefit of the elastic boundary. Afterward, the parametric studies are conducted to demonstrate the response amplitude advantages of the proposed BEH_EB, and the advantage of the potential energy distribution is mathematically interpreted. It is found that the elastic boundary brings additional dynamic coupling to reduce the depth of the potential energy well, which makes the BEH_EB easier to realize large-amplitude inter-well responses. Finally, the basin-of-attraction maps are presented to show the initial condition influence. The results show that the BEH_EB could enhance the occurring probability of the favorable inter-well responses in the low-frequency band, where the occurring probability could reach 100% at 2 and 3 Hz.